Loss of Identity and Nostalgia as Two Post-Impacts of Exile in Arabic and Spanish Poetry: Darwish and Cernuda as a Case Study - Abbaneh, Mohammad Daher (Technium Social Sciences Journal, 2023)
This comparative study aims at highlighting loss of identity and nostalgia as two exile’s post-impacts in Arabic and Spanish poetry. As exile is one of the recurrent themes in both cultures, the study has exclusively dedicated itself to investigate the loss of identity and nostalgia. In order to conduct the study, Darwish and Cernuda are selected to build the study on, as they have heavily referred to the above two post-impacts. The political situation that Palestine and Spain suffered from was the main motivation for the presence of exile in their poetry, respectively the external colonization in Darwish’s case and the Civil War in Cernuda’s. In order to practically conduct this comparative study, the author has selected a number of poems that share the same themes.